PENDIDIKAN POLITIK PADA ANAK USIA DINI (Studi Kasus di TK Pertiwi Teluk Kuantan Kecamatan Kuantan Tengah Kabupaten Kuantan Singingi Tahun 2020) - Sakinah, Huliqa; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
One of the agendas of President Joko Widodo's Nawa Cita is to strengthen the nation's character. The Minister of National Education of the Republic of Indonesia No. 58 of 2009 concerning Standards for Early Childhood Education covers the developmental environment: “Receiving language, expressing language and literacy. One level of development is: recognizing letter symbols. Connect pictures with words, show objects with words, read pictures that have words.The objectives of writing this thesis are: First, to find out political education in early childhood (Case Study at Pertiwi Teluk Kuantan Kindergarten, Kuantan Tengah District, Kuantan Singingi Regency in 2020). Second, to find out the obstacles in political education in early childhood ( Case Study in TK Pertiwi Teluk Kuantan, Kuantan Tengah District, Kuantan Singingi Regency in 2020). This research is a qualitative research. This research was conducted at Pertiwi Teluk Kuantan Kindergarten, Kuantan Tengah District, Kuantan Singingi Regency. The techniques used to collect data in this research are (1) Interview, (2) Observation, and (3) Document tracing.The conclusion of this study shows that Political Education in Early Childhood at Pertiwi Teluk Kuantan Kindergarten, Kuantan Tengah District, Kuantan Singingi Regency involves teachers as the main actors and the Kuantan Singingi Regency Education Office has duties, among others, overseeing the implementation of education, and setting educational service standards, providing writers with suggestions. so that the active role of the government represented by the Education Office and related parties in providing political education to early childhood becomes the initiator who gives deeper attention to existing educators and to parents is expected to protect the rights of children in the world of education. Keywords: Actors, Materials, Time, Political Education, Political Education Facilities and Infrastructure.